Social problems - Society for the Study of Social Problems (Berkely University of California Press, 1997)
From Journal webpage "Social Problems covers an extensive array of complex social concerns from race and gender to labor relations to environmental issues and human rights, it has been an important forum for sociological thought for over six decades.The journal brings to the forefront influential sociological findings and theories that have the ability to help us both better understand and better deal with our complex social environment.
Social problems is published four times yearly in February, May, August and November by the University of California Press for the society for the study of social problems. Full text articles are available from JSTOR​ https://www.jstor.org/journal/socialproblems
Keywords: Social problems and services; SOCIAL PROBLEMS; SOCIOLOGY; THEORY; SOCIAL ENVIRONMENT; SOCIAL WELFARE; PERIODICALS